THE CORRELATION BETWEEN STUDENTS’ LEARNING STYLE PREFERENCE AND LISTENING ACHIEVEMENT OF ENGLISH DEPARTMENT STUDENTS - Pikri, Vyvie Nurul; Aderlaepe, Aderlaepe; Siam, Siam (Journal of Teaching of English, 2020)
This research focused on the correlation between students’ learning styles and their listening achievement. The design was quantitative research. The research conducted in Halu Oleo University, English Department at academic year 2018/2019 that had passed Listening II to see their learning style and listening achievement. There were 76 students taken as samples. The data of the research were collected through a close-ended questionnaire adapted from Reid’s (1986) consisted of 30 statements and who had developed the perceptual learning style preference questionnaire to get the data of students’ learning style especially in listening II. To analyze the data, the researcher used descriptive statistics to find out the students’ listening achievement and their learning style based on the five categories; very good, good, moderate, low and failed. The researcher used the SPSS 16 program as the statistical program to analyze the data. The finding of the research showed that students’ listening achievement was mostly categorized as a good category and students were minor learning styles. Based on the discussion findings of this study that covered the score of students’ listening achievement and their learning style, the descriptive and inferential statistic analysis by using SPSS 16 program the researcher concluded that: Firstly, students the most preferred learning styles were Auditory Learning Style and Kinesthetic Learning Style. Secondly, based on the result above there were 2 learning style that correlate with listening achievement there were kinesthetic learning style showed that the coefficient correlate was -.317 and sig (2-tailed) was 0.038 ≤ 0.05 and group learning style showed that the coefficient correlates was -.0.366 and sig (2-tailed) was 0.01 ≤ 0.05. Also, the result of the correlation between students’ learning style and students' listening score showed that the coefficient correlation was -.349 and sig (2-tailed) was .022 it means that sig (2-tailed) ≤ 0.05 it means H1 was accepted so there was signifi couldt correlation. Meanwhile, coefficient correlates was negative correlate because the coefficient correlation was -.349. In addition, the researcher could conclude that there was a negative signifi couldt correlation between students’ learning style and their listening achievement of English Department Students at Halu Oleo University.